2022
DOI: 10.2147/jpr.s376575
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Changes of Paraspinal Muscles: A Comparative Study of Patients with Isthmic Spondylolisthesis, Patients with Degenerative Lumbar Spondylolisthesis, and Healthy Subjects

Abstract: Objective To investigate the differences, correlations, and clinical significance of the paraspinal muscles among patients with isthmic spondylolisthesis (IS), degenerative lumbar spondylolisthesis (DLS), and age-matched healthy subjects. Methods This study involved 159 age-matched patients with L4 anterior spondylolisthesis. The patients were divided into the IS group (n = 81) and DLS group (n = 78). Eighty-four age-matched healthy adults were enrolled as the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Although the paraspinal muscles in patients with isthmic spondylolisthesis (IS) and DLS showed varying degrees of degeneration [ 114 ], they might play an important role in maintaining the structure and function of the spine in patients with DLS and IS. Some retrospective research has provided support for this viewpoint.…”
Section: Paraspinal Muscles and Thoracic/lumbar Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the paraspinal muscles in patients with isthmic spondylolisthesis (IS) and DLS showed varying degrees of degeneration [ 114 ], they might play an important role in maintaining the structure and function of the spine in patients with DLS and IS. Some retrospective research has provided support for this viewpoint.…”
Section: Paraspinal Muscles and Thoracic/lumbar Disordersmentioning
confidence: 99%
“…Some retrospective research has provided support for this viewpoint. Low FI and high CSA of the paraspinal muscles might have a protective effect against the development of DLS and IS [ 114 ]. In addition, larger CSAs of MF and PS might be protective factors to prevent lumbar stability in patients with isthmic spondylolisthesis [ 115 ].…”
Section: Paraspinal Muscles and Thoracic/lumbar Disordersmentioning
confidence: 99%
“…Even patients with different type of spondylolisthesis (IS vs. DS) had different CSA and fatty infiltration patterns in their paraspinal muscles. Li et al [16] depicted that patient with IS and control subjects had bigger erector spinae muscles than those with DS. Cao et al [17] suggested that fatty infiltration in the psoas was an independent factor related to DS in asymptomatic adults.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al [17] suggested that fatty infiltration in the psoas was an independent factor related to DS in asymptomatic adults. However, they evaluated paraspinal muscles at only L4-L5 level [15][16][17]. A recent study showed multifidus degeneration was more significant in patients with lumbar DS compared to those with degenerative lumbar kyphosis [18].…”
Section: Introductionmentioning
confidence: 99%